2022
DOI: 10.3389/fnut.2022.1066411
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between serum 25-hydroxy-vitamin D levels and anti-SARS-CoV-2 S-RBD IgG and neutralizing antibody levels among cancer patients receiving COVID-19 vaccines

Abstract: IntroductionDuring the coronavirus disease 2019 (COVID-19) pandemic, vitamin D has been established as an immune-modulator that reduces pro-inflammatory damage which effectively diminish the severity of COVID-19. Vitamin D also has a significant effect against influenza and dengue and increase the seroconversion following influenza vaccination. To date, the role of vitamin D in optimizing the efficacy of COVID-19 vaccines remains unclear. This study aimed to analyze the correlation between serum 25-hydroxy-cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 92 publications
(127 reference statements)
1
12
0
Order By: Relevance
“…Unlike iron and zinc, serum concentrations of fat-soluble vitamins (A, D, and E) in our study displayed no significant association with either vaccine-specific antibody binding affinity or neutralizing ability against SARS-CoV-2 virus. This aligns with some existing research on COVID-19 vaccination,[21][22][23][24][25] but contrasts with others reporting positive associations between vitamin D and antibody responses [18][19][20]. These discrepancies might stem from variations in study populations, including pre-existing vitamin D status, vaccination schedules (primer vs. booster dose), vaccine type (inactivated vs. mRNA), and even participant age 23,24.…”
supporting
confidence: 77%
“…Unlike iron and zinc, serum concentrations of fat-soluble vitamins (A, D, and E) in our study displayed no significant association with either vaccine-specific antibody binding affinity or neutralizing ability against SARS-CoV-2 virus. This aligns with some existing research on COVID-19 vaccination,[21][22][23][24][25] but contrasts with others reporting positive associations between vitamin D and antibody responses [18][19][20]. These discrepancies might stem from variations in study populations, including pre-existing vitamin D status, vaccination schedules (primer vs. booster dose), vaccine type (inactivated vs. mRNA), and even participant age 23,24.…”
supporting
confidence: 77%
“…11 Indeed, we could not find any association between native Vitamin D 3 levels, or prescription of activated vitamin D analogues and the median IC50 response following one or two vaccinations against COVID-19 for any of the variants tested. Previous studies have reported variable results, with some reporting that the vaccination response to COVID-19 was reduced by having lower levels of Vitamin D 3 , 13,14 and others observing no effect. 15,16 This study is the first to investigate whether Vitamin D 3 or the prescription of activated forms of Vitamin D have affect the response to COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 96%
“…Although several studies have reported an association between low levels of Vitamin D 3 and the response to COVID-19 vaccination, 13,14,22 particularly studies in pati-ents with cancer. 23 Haemodialysis patients are recognised to have lower responses to vaccination compared to the general population, 9 and although many haemodialysis patients have low levels of Vitamin D 3 , any potential effect of Vitamin D may have been obscured by the overall poor response rates to vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Zitt E. and colleagues illustrated that CKD patients with serum vitamin D levels below 10 ng/mL exhibited a reduced seroconversion rate when administered the hepatitis B vaccine [51]. Vitamin D may also impact serological response against SARS-CoV-2 [52], but the role of the response to the anti-SARS-CoV-2 vaccine remains unclear. Furthermore, the obtained results are controversial.…”
Section: Discussionmentioning
confidence: 99%